Ufer grounding system to minimize risk of lightning strike using concrete mixed with bentonite and coconut fiber - Martin, Yul; Permata, Diah; Ulya, Annisa; Despa, Dikpride; Marwansyah, Marwansyah; Rahmat, Ali (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2020)
The increasing frequency of lightning strikes endangers human safety and life. The grounding system was introduced to face the lightning strikes. This research aimed to understand the changes of grounding resistance value using concrete mixed with bentonite and coconut fiber. The research was conducted in the Laboratory of Electrical Engineering, University of Lampung. The research was started from October 2017 to April 2018. This research used the Ufer grounding system. Concretes with (25 x 25 x 30) cm3 in volume were planted at a depth of 50 cm with copper-coated electrodes that were 16 mm in diameter. 4 concrete was produce with different component T1= concrete, 30% bentonite, T2= concrete, 30% bentonite, 1.5% coconut fiber, T3= concrete, 30% bentonite, 0.75% coconut fiber, T4= concrete + 1.5% coconut fiber. The results show that the lowest grounding resistance values were 45.896 Ω on the concrete with bentonite: cement: sand: gravel = 0.3: 0.7: 2: 4. By adding 1.5% coconut fiber, the grounding resistance value is 3.5 times smaller than the grounding resistance values of the soil (161.2 Ω). Adding bentonite and coconut fiber can decrease the grounding resistance values